Accessibility to tuberculosis treatment: assessment of health service performance (Revista Latino-Americana de Enfermagem, 2011)
The aim of this study was to assess the accessibility of patients to the treatment of tuberculosis in Ribeirão Preto, countryside of São Paulo State. Evaluation study type, with a quantity approach. Interviews with 100 patients initiated on anti-tuberculosis chemotherapy between 2006-2007 were conducted, using a structured questionnaire based on the Primary Care Assessment Tool (PCAT). Data were analyzed through variance analysis. There was a positive feedback regarding to organizational accessibility, however, the performance of health services has been unsatisfactory in providing transportation vouchers and in addressing the need to use transport for displacement to the health unit, resulting in indirect costs to patients. The services with the highest number of patients treated were those with higher irregularity in the conduct of home visits, showing that the availability of resources (human, material and time) and the organization of care may influence the accessibility to treatment.